A COMPARATIVE STUDY OF TEACHERS’ JOB SATISFATION OF CHEA SIM BOEUNG KENG KANG AND CHEA SIM ANGKOR CHEY UPPER SECONDARY SCHOOLS IN CAMBODIA - Sothina, King; Ye, Yan (Scholar: Human Sciences, 2015)
This study was conducted to compare the teachers’ job satisfaction towards work itself, work group, working condintion, and supervision between the two selected Upper Secondary Schools in Cambodia, Chea Sim Boeung Keng Kang in Phnom Penh and Chea Sim Angkor Chey in Kampot province. The collected data was analyzed by Frequency, Percentage, Mean, Standard deviation; and Independent Samples (two-tails) t-test. The result found that there was significant difference of teachers’ job satisfaction between Chea Sim Boeung Keng Kang and Chea Sim Angkor Chey Upper Secondary Schools in Cambodia at the probability .024 of significance. Furthermore, significant difference of teachers’ job satisfaction towards work group was also found in the two schools. The mean of overall teachers’ job satisfaction of Chea Sim Boeung Keng Kang Upper Secondary School was observed higher than the mean of overall teachers’ job satisfaction of Chea Sim Angkor Chey Upper Secondary School. However, the means of teachers’ job satisfaction of the two schools toward working condition were observed to be the highest, while supervision to be the lowest level.